Defense Spending and Economic Growth:A Theoretical Manifestation for Empirical Studies - I. Hakan Yetkiner (Izmir University of Economics, Department of Economics, 2012)
Defense literature is still in need of a theoretical framework in the neoclassical sense, in regard to empirical research on the relationship between defense spending and economic growth. In this respect, Dunne, Smith and Willenbockel (2005), although not without technical problems, represented a breakthrough in the field. In addition, the whole empirical literature following Mankiw, Romer and Weil (1992) is based on the unrealistic assumption that technological progress is identical across countries and constant in time. Recently, Bayraktar-Saglam and Yetkiner (2012) developed a theoretical framework that overcomes the unrealistic assumption of constant and identical rates of technological progress. In this paper, we achieve two things. First, we develop the true growth-defense model, based on Dunne, Smith and Willenbockel (2005). Second, we overcome the general weakness of constant and identical technological progress assumption in empirical growth studies by employing Bayraktar-Saglam and Yetkiner (2012) growth framework. We show that the intensity of defense spending in GDP has both positive and negative effects. In this respect, the theory supports the findings of the empirical literature, which are inconclusive in nature.
Keywords: H56; O30; O41; O47; O50; 330; Military Expenditure; Defense Spending; Convergence; Economic Growth; Militärausgaben; Wirtschaftswachstum; Technischer Fortschritt; Wirtschaftliche Konvergenz; Wachstumstheorie